Analysis of agrarian policy in Algeria: from independence to nowadays - KAABACHE, Rachida; BADAOUI, Brahim (Journal of Human Sciences, 2022)
Agriculture is a structured body, through which individuals can satisfy their alimentary needs by adequate land policy. In Algeria, many reforms have been carried however; the country remains dependent of foreign states regarding alimentary. In addition, it’s living a demographic and epidemiological transition. That puts the country in a precarious situation, especially during international crises. In that, a revision of the land policy is to be considered in order to overcome all its shortcomings. To conclude, we are aiming through this paper to present a preventive approach, suggesting an analysis of Algerian land politics, framed between independence and present day, with a critic of its effect on the alimentary availability, nutritional and individuals’ health, and to propose recommendations.